1982
DOI: 10.1007/bf00377129
|View full text |Cite
|
Sign up to set email alerts
|

Arctic tundra: A source or sink for atmospheric carbon dioxide in a changing environment?

Abstract: Intact cores from the wet coastal arctic tundra at Barrow, Alaska, were used as microcosms in the measurement of CO fluxes between peat, vegetation, and atmosphere under controlled conditions. Net ecosystem CO uptake was almost twice as high at present summer temperatures (4° C) than at 8°. Lowering the water table from the soil surface to -5 cm also had a pronounced effect in decreasing net ecosystem carbon storage. Warming of the tundra climate could change this ecosystem from a sink for atmospheric CO to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
213
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(233 citation statements)
references
References 13 publications
19
213
1
Order By: Relevance
“…Data from the in situ manipulations at Prudhoe Bay dramatically demonstrated that soil drainage results in increased net C02 efflux due primarily to more rapid rates of soil respiration. Similar results have k e n previously demonstrated using laboratory soil incubations (Billings et al, 1982;Freeman et al, 1993; Funk et al, 1994) and in drained peatlands (Silvola, 1986;Hogg et aL, 1992). Jn the Toolik Lake manipulations, however, draining (or diverting) soil water lead to reduced ntes of net CO2 efflux, due primarily to enhanced GPP of drained plots.…”
Section: Hypothesissupporting
confidence: 83%
See 1 more Smart Citation
“…Data from the in situ manipulations at Prudhoe Bay dramatically demonstrated that soil drainage results in increased net C02 efflux due primarily to more rapid rates of soil respiration. Similar results have k e n previously demonstrated using laboratory soil incubations (Billings et al, 1982;Freeman et al, 1993; Funk et al, 1994) and in drained peatlands (Silvola, 1986;Hogg et aL, 1992). Jn the Toolik Lake manipulations, however, draining (or diverting) soil water lead to reduced ntes of net CO2 efflux, due primarily to enhanced GPP of drained plots.…”
Section: Hypothesissupporting
confidence: 83%
“…flux across the Haul Road transect suggest that elevated temperature leads to an increase in net C02 efflux. In laboratory incubations of wet sedge microcosms, a 4 "C increase in temperature was found to result in a significant decrease in net C storage (Billings et al, 1982 (Oechel et a/., in press B), lending support to the above hypothesis. In the Toolik Lake manipuiation, elevated temperature lead to greater net efflux, regardless to the water table manipulation.…”
mentioning
confidence: 80%
“…Although it is believed that soil carbon emission may be enhanced by the global warming for its temperature effect (Billings et al, 1982;Schleser, 1982;Raich and Schlesinger, 1992;Kirschbaum, 1995), it is possible that the presumed enhancement of soil respiration may be offset by the soil moisture effect as shown in our results. The overall effect can only be adequately evaluated by treating the temperature sensitivity measure as a function of, at least, temperature and moisture.…”
Section: Discussionmentioning
confidence: 62%
“…Soil moisture exerts a control on tundra ecophysiology through production, decomposition and nutrient cycling (Miller et al 1984), and a lowered water-table and increased thaw might be expected to accelerate the rate of soil decomposition (CO 2 source) over photosynthesis (CO 2 sink), so that the balance in tundra soils shifts from one of C-input, or storage, to C-output (Billings et al 1982(Billings et al , 1983Johnson et al 1996). If the effect of decomposition were to increase nutrient availability, there may be an additional uptake of CO 2 owing to higher rates of photosynthesis (Shaver & Chapin 1986;Shaver et al 1998;Johnson et al 2000), although as sink strength in vascular plants decreases, productivity may be offset by substrate-controlled or nutrient-limited CO 2 loss from soil respiration by microorganisms (Nadelhoffer et al 1991;Hobbie 1996;Jonasson et al 1999).…”
Section:      mentioning
confidence: 99%